Identifikasi Lahan Pertanian Pangan Berkelanjutan di Kabupaten Gowa, Sulawesi Selatan: Zonasi Lingkup Kawasan Mamminasata Menggunakan Pendekatan MCDM - Zulkarnain Chairuddin (Universitas Hasanuddin, 2018)
The protection of agricultural land is very important to be studied scientifically considering the rapid growth of the population so that the possibility of land use conflict is very high. The main purpose of this research is to identify and inventory agricultural land of food especially existing rice-paddy fields to find zonasi agricultural land for sustainable foodcrops (ALSF) and agricultural reserved land for sustainable foodcrops (ARLSF)) with the level of threat from the transfer function in Gowa Regency area of hinterland Mamminasata, South Sulawesi. This study used a multiple criteria decision making approach with purpose mapping function of ALSF and ARLSF. The generic attributes, from: the biophysical aspects of the land (altitude, sizes of soil cracking, length of rice-field in slope landscape unit, proportion of paddy field area, top soil thickness), and socio-economic aspects (population density, population growth rate, demand for paddy field, productivity of paddy fields, equilibrium of paddy field), and policy aspects (local regulations status, detailed spatial plan status, type of irrigation networks). While the scenario of zonation of ALSF and ARLSF is used the criteria of distance from the provincial capital (Makassar) and the district capital (Sombaopu), the status of the rice-paddy field equilibrium and the trend pattern of percentage of space requirement. The results of the research shows that the existing position of paddy field is identified as ALSF and ARLSF zonation currently 24,210 Ha. The level of vulnerability of land conversion, which is in a